Employee Engagement and Transactional Leadership Style and Its Influence on Satisfaction Employee Work Moderated by Fairness OrganizationAt PDAM Tirtanadi Medan - Lubis, M. Al Hafis; Junita, Audia; Bulan, Tapi Rondang Ni (Cattleya Darmaya Fortuna, 2023)
This study aims to determine the effect of employee engagement and transactional leadership style on job satisfaction of PDAM Tirtanadi Medan employees. To find out whether organizational justice moderates the effect of employee engagement and transactional leadership style on employee job satisfaction at PDAM Tirtanadi Medan. The total population in this study amounted to 266 people, and by using the Slovon formula, a sample of 144 people was obtained. The analysis technique used is multiple linear regression and MRA. The results showed that employee engagement and transactional leadership style had a positive and significant effect on employee job satisfaction at PDAM Tirtanadi Medan. Organizational justice weakens employee engagement and strengthens transactional leadership style on employee job satisfaction at PDAM Tirtanadi Medan